Kepastian Hukum Kepemilikan Hak Cipta Atas Karya Artificial Intelligence: Analisis Kekosongan Norma dalam Undang-Undang No. 28 Tahun 2014 - Ditha Maharani; Moh. Wazir Kamil; Yuyun Meliyani; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the legal status of Artificial Intelligence-based works within the Indonesian copyright system, identify gaps in the legal framework regarding copyright ownership of AI works under Law No. 28 of 2014 on Copyright, and formulate directions for legal reform to ensure legal certainty in the digital age. The study employs a normative legal methodology with legislative, conceptual, and comparative approaches through an analysis of legislation, legal doctrine, court decisions, and scholarly literature related to Artificial Intelligence and intellectual property rights. The research findings indicate that Indonesia’s copyright legal system remains rooted in the human authorship paradigm, which positions humans as the sole creators; consequently, works generated by generative AI have not yet received legal certainty regarding protection. This regulatory gap creates ambiguity regarding ownership attribution, economic rights, moral rights, and legal liability in the commercialization of AI-based digital works. This study underscores the need for a reconstruction of copyright law through the reformulation of the concept of the creator, the redefinition of the principle of originality, and the establishment of adaptive and transformative Artificial Intelligence regulations to maintain a balance between technological innovation, intellectual property protection, and national legal certainty.